2022
DOI: 10.2147/bctt.s380579
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Intraoperative Frozen Section Analysis of Sentinel Lymph Nodes Necessary in Every Early-Stage Breast Cancer?

Abstract: Clinical application of the ACOSOG Z0011 trial results allows clinically node-negative breast cancer patients who meet criteria to avoid axillary dissection even when 1-2 sentinel lymph nodes (SLNs) are positive for metastatic disease. Intraoperative frozen section (iFS) analyses of SLNs were thought to reduce re-operation rates despite variable reported sensitivity and possibility of a false negative result. This study evaluated the rate of re-operations prevented by SLN iFS in a tertiary care hospital in Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…The primary objective of utilizing iFS is to minimize the need for a second operation. Studies have reported a false negative rate (of having less than 2 positive nodes) of 2-4% for iFS compared to PS [8, 9,14]. In our study, we observed a discordance rate of 4.9% between metastatic nodes detected on iFS and PS, but none of them exceeded a discrepancy of 2 positive nodes.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The primary objective of utilizing iFS is to minimize the need for a second operation. Studies have reported a false negative rate (of having less than 2 positive nodes) of 2-4% for iFS compared to PS [8, 9,14]. In our study, we observed a discordance rate of 4.9% between metastatic nodes detected on iFS and PS, but none of them exceeded a discrepancy of 2 positive nodes.…”
Section: Discussioncontrasting
confidence: 41%
“…However, recent studies suggest that iFS may be unnecessary in early-stage breast cancer patients, where tumor size and axillary lymph node status can be used as prognostic factors [8,17]. This trend has already been observed in lumpectomy cases, where iFS has been found to confer minimal diagnostic value, in accordance with the ACOSOG criteria [13,14]. A recent randomized controlled trial conducted by The European Institute of Oncology of Milan (SOUND trial) even con rmed the safety of omitting SLNB in well-selected early-stage breast cancer patients who were treated with breast-conserving surgery and had no evidence of axillary node involvement by clinical and ultrasound evaluation [18].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, the reduction of the operative time may allow one or two more procedures to be scheduled every day in the surgical theatre, with considerable economical savings and boosted clearance of the waiting list. The reduction in health care costs associated with this change in management of SLNBs has also been highlighted by others (20,(36)(37)(38)(39)(40). However, others reported opposite conclusions, claiming an increase in costs with the use of PS-SLNB in consideration of a higher reoperation rate (41).…”
Section: Discussionmentioning
confidence: 80%
“…Intraoperative pathologic assessment of SLNs requires skilled pathologists and equipment, which increases the surgical time and costs. Moreover, following the results of the Z0011 study, intraoperative frozen section analysis of SLNs in patients undergoing conservative breast surgery is considered inappropriate [16,17] . This is due to both the low sensitivity of the method (from 66.7% to 95.8%) and a wide range of false negative results (from 5.5% to 43%) [17,18] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, following the results of the Z0011 study, intraoperative frozen section analysis of SLNs in patients undergoing conservative breast surgery is considered inappropriate [16,17] . This is due to both the low sensitivity of the method (from 66.7% to 95.8%) and a wide range of false negative results (from 5.5% to 43%) [17,18] . For the study of permanent sections, its main disadvantage is the need to perform a repeat operation in patients with ALN metastases.…”
Section: Discussionmentioning
confidence: 99%